The ideology of instructional leadership among principals on student academic achievement - Mohamad Yasin, Murni; Ali Bashah, Mohd Helmi; Zainal, Hasny @ Yanti; Lope Pihie, Zaidatol Akmaliah; Fooi, Foo Say; Basri, Ramli (Finlogy Publication, 2016)
Malaysian education system has come under public scrutiny and debate, their concern regarding not only the system but also the teachers and administrators to adequately prepared young Malaysian for the 21st century. The purpose of the study is to explore the knowledge base or the ideology about effective instructional leadership among the principals and with this ideology how they practice their instructional leadership on student achievement. The study also want to investigate is there any changes on principals instructional leadership practices due to the astonishing impact of ICT and globalization. This study is hoped to be able to assist the principals in reevaluating the strengths and weaknesses of their instructional leadership practices so that not only can increase student achievement in Malaysian Education System but also increase in global standard. The methodology is a qualitative study in which interviews were conducted with 3 purposive principals in Seremban district. Result indicated that purposive principals were understood instructional leadership as synonymous with clear vision and goal, be a role model, classroom supervision, supporting and listening but they not elaborated about school climate. However their goal and vision is not toward globalization but still answerable to the system of exam-oriented and lacking of culture on learning and professional behavior which been too long in Malaysian society.